Individual Perceptions of Adolescents in Efforts to Prevent Hypertension - Eko Rustamaji Wiyatno; Siti Nur Kholifah; Dyah Wijayanti; Nikmatul Fadilah (Health Notions, 2022)
The unhealthy behavior of adolescents today tend to be more at risk of causing the incidence of non-communicable diseases, including hypertension, e.g. alcohol consumption, smoking, lack physical activity, and poor diet. The unhealthy behaviours very often relate with the negative perception of a healthy lifestyles. The aim of the study was to describe individual perceptions in the prevention of hypertension among adolescents. The study used cross-sectional design. A sample of 210 students was taken from 2nd grade junior high school in Surabaya through multistage sampling. The variable included individual perception in the prevention of hypertension involve the perceived susceptibility and the perception of seriousness. Instrument used was a questionnaire with closed-ended questions. Descriptive analysis was used to represent the individual perceptions in the prevention of hypertension. The perceived susceptibility to hypertension was mostly good (99.5%), and the perception of seriousness of hypertension was half good (51.4%). Adolescents' perceptions can provide an estimate of the prevention of hypertension. One of the factors influencing adolescents' perception of hypertension is related to knowledge. In order to achieve a positive perception in the prevention of hypertension, the support of schools through the program of School Health Unit and collaboration with the Community Health Center through health education is necessary to improve the understanding of the prevention of hypertension in adolescents. Keywords: individual perception; adolescent; hypertension